Immunisation with modified HPV16 E7 genes against mouse oncogenic TC-1 cell sublines with downregulated expression of MHC class I molecules - Smahel, Michal; Síma, Pavel; Ludvíková, Viera; Marinov, Iuri; Pokorná, Dana; Vonka, Vladimír (Vaccine, 2003)
Human papillomavirus type 16 (HPV16)-transformed mouse TC-1 cells are extensively used in the evaluation of efficacy of experimental vaccines against tumours induced by HPVs. As these cells strongly express MHC class I molecules and downregulation of MHC class I surface expression is one of the important mechanisms that enable tumour escape from the host immune system, we undertook to derive TC-1 clones with reduced expression of MHC class I antigens. TC-1 cells were inoculated into mice preimmunised with an E7 gene-based DNA vaccine and from tumours developing in a portion of the animals, cell clones with downregulated MHC class I surface expression were isolated. Treatment with IFN-gamma resulted in an upregulation of MHC class I molecules in these cells, but after IFN-gamma removal, their expression gradually dropped again. When the expression of some components of the antigen-processing machinery (APM; LMP-2, TAP-1, and TAP-2) was tested, a reduced TAP-1 production was detected in cell lines with downregulated MHC class I expression. An enhanced immunoresistance of TC-1-derived clones with reduced MHC class I expression was observed in animals immunised with plasmids carrying modified E7 genes. Apart from the previously described fusion gene Sig/E7/LAMP-1, a new construct, Sig/E7GGG/LAMP-1, with a mutated Rb-binding site, was also used for immunisation. No significant change of immunogenicity was recorded for Sig/E7GGG/LAMP-1. Cell lines with downregulated MHC class I expression derived from TC-1 cells may represent a useful model for testing therapeutic anti-HPV vaccines in settings more relevant to clinical requirements.
Keywords: genetická transkripce; imunizace; Biolistics; geny ras; Genes, ras; regulace genové exprese u nádorů; Neoplasms, Experimental; Genes, Synthetic; geny MHC třídy I; Transcription, Genetic; H-2 antigeny; onkogenní proteiny virové; Cell Line, Transformed; virová transformace buněk; Female; polymerázová řetězová reakce s reverzní transkripcí; Lung; biolistika; Recombinant Proteins; Reverse Transcriptase Polymerase Chain Reaction; zvířata; transformované buněčné linie; myši; represorové proteiny; plíce; Antigens, Neoplasm; myši inbrední C57BL; Oncogene Proteins, Viral; Vaccines, DNA; Mice; antigeny nádorové; Genes, MHC Class I; Papillomaviridae; Antigen Presentation; rekombinantní proteiny; Papillomavirus E7 - proteiny; H-2 Antigens; Cell Transformation, Viral; ženské pohlaví; Repressor Proteins; experimentální nádory; Neoplasm Transplantation; protinádorové vakcíny; transplantace nádorů; Cancer Vaccines; Mice, Inbred C57BL; Immunotherapy, Active; interferon gama; syntetické geny; aktivní imunoterapie; Animals; DNA vakcíny; Gene Expression Regulation, Neoplastic; Papillomavirus E7 Proteins; Interferon-gamma; Immunization; prezentace antigenu